The Role of Microcirculatory Dysfunction During Paclitaxel Treatment as a Critical Co-Factor for the Development of Chemotherapy-Induced Peripheral Neuropathy - Reuter, Susanne; Bajorat, Rika; Müller-Graf, Fabian; Zitzmann, Amelie R.; Müller, Volkmar; Pickhardt, Anna-Lena; Reuter, Daniel A.; Böhm, Stephan H.; Vollmar, Brigitte (Geburtshilfe und Frauenheilkunde, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) has a lasting impact on quality of life with a high prevalence and the lack of preventive and causal treatment options. In addition, they are often dose-limiting for curative and palliative oncological therapy. The aim of this study was to systematically investigate the occurrence of paclitaxel-induced peripheral microcirculatory dysfunction and its potential impact on peripheral neuropathy using an experimental in vivo approach.77 female 8-week-old mice were randomly assigned into three groups. Each group was exposed to the following intraperitoneal interventions in a blinded fashion: The therapy group was treated with six cycles of paclitaxel. In the control group, mice received six cycles of saline solution. In the vehicle group, animals received six cycles of cremophor. Various microscopic, neurological and biochemical analyses were performed to assess the effects on peripheral nerve function, microcirculation and inflammation.Von Frey’s neurological test showed a progressive peripheral neuropathy with a significant change in the sensitivity in the sense of hypesthesia of the hind paws in mice treated with paclitaxel. Beside signs of systemic inflammation, intravital microscopic analysis showed a significant reduction in functional capillary density, increased venular leukocyte adherence and endothelial permeability in the paclitaxel-treated mice compared to the control groups. In addition, serological tests and histopathological examinations underlined the paclitaxel-induced inflammation and nerve damage as well as the disturbance of the microcirculation.The presented findings suggest that paclitaxel-induced microcirculatory disturbances may contribute to the development and severity of CIPN, highlighting the importance of considering microvascular and inflammatory mechanisms in the pathogenesis and management of chemotherapy-induced neuropathy.
Keywords: chemotherapy-induced peripheral neuropathy (CIPN); paclitaxel; intravital fluorescence microscopy; microvascular damage; endothelial lesions; inflammation